2007
DOI: 10.1074/jbc.m704618200
|View full text |Cite
|
Sign up to set email alerts
|

A Triplex-forming Sequence from the Human c-MYC Promoter Interferes with DNA Transcription

Abstract: Naturally occurring DNA sequences that are able to form unusual DNA structures have been shown to be mutagenic, and in some cases the mutagenesis induced by these sequences is enhanced by their transcription. It is possible that transcription-coupled DNA repair induced at sites of transcription arrest might be involved in this mutagenesis. Thus, it is of interest to determine whether there are correlations between the mutagenic effects of such noncanonical DNA structures and their ability to arrest transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 44 publications
(16 reference statements)
6
118
0
Order By: Relevance
“…We have recently reported that an S1-sensitive element from the c-MYC promoter, which has the potential to form either a H-DNA or a quadruplex structure, blocks T7 RNA polymerase in an in vitro assay, resulting in partial transcription product arrest. Further, various nucleotide substitutions were introduced to specifically destabilize either the triplex structure or the quadruplex structure, and the result suggested that the triplex structure, but not quadruplex, was responsible for the transcription arrest [155].…”
Section: H-dna Is Implicated In Transcription Regulationmentioning
confidence: 99%
“…We have recently reported that an S1-sensitive element from the c-MYC promoter, which has the potential to form either a H-DNA or a quadruplex structure, blocks T7 RNA polymerase in an in vitro assay, resulting in partial transcription product arrest. Further, various nucleotide substitutions were introduced to specifically destabilize either the triplex structure or the quadruplex structure, and the result suggested that the triplex structure, but not quadruplex, was responsible for the transcription arrest [155].…”
Section: H-dna Is Implicated In Transcription Regulationmentioning
confidence: 99%
“…Although the in vivo existence of DNA:RNA triplexes and their role in epigenetic programming still need to be validated, our study provides novel mechanistic insights into the mode of action of ncRNA in chromatin-based processes, implicating a direct and possibly widespread role of RNA:DNA structures in epigenetic regulation. In support of this view, triple-helix target sites were found to be overrepresented at human gene promoters, highlighting the potential of naturally occurring hydrogen bond interactions of ncRNA with the major groove of DNA to control gene expression (Goñ i et al 2004;Belotserkovskii et al 2007). A triplex-mediated mechanism of DNA methylation and gene silencing is particularly intriguing considering that the vast majority of the transcriptional output of the human genome represents ncRNA (Prasanth and Spector 2007;Bü hler 2009;Mattick 2009).…”
mentioning
confidence: 78%
“…Purification of transcription substrates was as described in ref. 31. Unless otherwise stated, in transcription experiments with linear DNA we used plasmid templates linearized by Dra III restriction digestion 0.96 kb downstream from the promoter.…”
Section: Methodsmentioning
confidence: 99%